Computer method of description of technologies and properties of thermoelectric Bi2-Te3 based material by extrusion method - Rybchakov, D.E. (Journal of Thermoelectricity, 2023)
This paper presents the results of a study of literature sources which describe the technology and properties of thermoelectric materials obtained by extrusion method. The result of one of the stages of creating a software product to describe the technologies for obtaining of a thermoelectric materials based on Bi-Te compounds and their properties are presented. Bibl. 7, Fig.4, Tabl.1.